Incremento poblacional de Myzus persicae (Sulzer) sobre tres crucíferas hortícolas en laboratorio - Vasicek, Araceli (2003)
Cohorts of Myzus persicae (Sulzer) were reared on Raphanus sativus, Brassica oleracea var. capitata and B. oleracea var. italica at 10 ± 1ºC, 90% relative humidity and a 12:12 h photoperiod. Under these conditions significant statistical differences were found between intrinsic growth rates (rm), which reached a maximum of 0.082, 0.045 and 0.028 females female-1 d-1 on R. sativus, B. oleraceea var. italica and B. oleracea var. capitata, respectively, and net reproductive rates (Ro) were 26, 6 and 3.4 females female-1 generation-1, respectively. M. persicae needs ca. around 8 days to duplicate numbers (D) on R. sativus and 16 and 30 days on B. oleracea var. italica and B. oleracea var. capitata, respectively. Results indicated this the aphid could reach greater population levels on R. sativus than on the other cruciferous plants during the fall and winter seasons, and an intercrop cultivation with other cruciferous plants could be recommended if it is the main crop. On the other hand, R. sativus is a winter weed for other vegetable crops, and thus early control could reduce posterior dispersion of the aphid.